Flavonoid-Labeled Biopolymer in the Structure of Lipid Membranes to Improve the Applicability of Antioxidant Nanovesicles - Patrick D. Mathews; Gabriella S. Gama; Hector M. Megiati; Rafael R. M. Madrid; Bianca B. M. Garcia; Sang W. Han; Rosangela Itri; Omar Mertins (MDPI AG, 2024)
Nanovesicles produced with lipids and polymers are promising devices for drug and bioactive delivery and are of great interest in pharmaceutical applications. These nanovesicles can be engineered for improvement in bioavailability, patient compliance or to provide modified release or enhanced delivery. However, their applicability strongly depends on the safety and low immunogenicity of the components. Despite this, the use of unsaturated lipids in nanovesicles, which degrade following oxidation processes during storage and especially during the proper routes of administration in the human body, may yield toxic degradation products. In this study, we used a biopolymer (chitosan) labeled with flavonoid (catechin) as a component over a lipid bilayer for micro- and nanovesicles and characterized the structure of these vesicles in oxidation media. The purpose of this was to evaluate the in situ effect of the antioxidant in three different vesicular systems of medium, low and high membrane curvature. Liposomes and giant vesicles were produced with the phospholipids DOPC and POPC, and crystalline cubic phase with monoolein/DOPC. Concentrations of chitosan-catechin (CHCa) were included in all the vesicles and they were challenged in oxidant media. The cytotoxicity analysis using the MTT assay (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide) revealed that concentrations of CHCa below 6.67 µM are non-toxic to HeLa cells. The size and zeta potential of the liposomes evidenced the degradation of their structures, which was minimized by CHCa. Similarly, the membrane of the giant vesicle, which rapidly deteriorated in oxidative solution, was protected in the presence of CHCa. The production of a lipid/CHCa composite cubic phase revealed a specific cubic topology in small-angle X-ray scattering, which was preserved in strong oxidative media. This study demonstrates the specific physicochemical characteristics introduced in the vesicular systems related to the antioxidant CHCa biopolymer, representing a platform for the improvement of composite nanovesicle applicability.